Respostas
respondido por:
2
(x + 59)/(x + 17) = (x + 17)/(x + 3)
(x + 17)² = (x + 59)(x + 3)
x² + 34x + 17² = x² + 62x + 177
34x + 289 = 62x + 177
28x = 112
x = 4
A sequencia é : 7,21,63
(x + 17)² = (x + 59)(x + 3)
x² + 34x + 17² = x² + 62x + 177
34x + 289 = 62x + 177
28x = 112
x = 4
A sequencia é : 7,21,63
respondido por:
1
P.G. (x+3, x+17, x+59) Propriedade: o quadrado do termo médio (x+17)
é igual ao produto dos extremos.
(x + 17)² = (x + 3).(x + 59)
x² + 2.x.17 + 17² = x² + 59.x + 3.x + 3.59
x² + 34.x + 289 = x² + 62.x + 177
x² - x² + 34.x - 62.x = 177 - 289
- 28.x = - 112
x = - 112 : ( - 28)
x = 4 (resposta) P.G. (7, 21, 63), razão = 3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás